Contextual Moderation of Racial Bias The Impact of Social Roles on Controlled and Automatically Activated Attitudes.[articles]. - Barden, Jamie
Three experiments tested the hypothesis that the social roles implied by specific contexts can attenute or reverse the typical pattern of racial bias obtained on both controlled and automatic evaluation measures. Study 1 assessed evaluations of Black and Asian faces in contexts related to athlete or student roles. Study 2 compared evaluations of Black and Wfaces in 3 role-related contexts (prisoner, churchgoer and factory worker). Study 3 manipulated role cues (lawyer or prisoner) within the same prison context. All 3 studies produced significant reversals of racial bias as a function or implied role on measures of both controlled and automatic evaluation. These results support the interpretation that diffirential evaluations based on Race x Role interactions provide one way that context can moderate both controlled and automatic racial bias. -- (from the author)
Keywords: Psychology-Periodicals.